Creating an Effective Bureaucracy by Reducing Bureaucratic Pathology in Local Governments - Endang Try Setyasih (Global Writing Academica Researching and Publishing, 2023)
These factors, which are collectively referred to as sick bureaucracy or bureaucratic pathology, are experienced in local government bureaucracies and include convoluted work procedures, uneven workload, slowness, inefficiency, rigidity, lack of transparency, and corrupt behavior. The bureaucratic pathology that currently exists within the Department of Population and Civil Registration of the local government of Cianjur Regency is going to be reduced as a primary objective of this study. The reduction of this pathology will allow for the creation of a more efficient bureaucracy. This method can also be used to obtain insight into something little is known about, and it can assist researchers supply complicated details about phenomena that are difficult to define. This type of research is a type of qualitative research where this method can also be employed. The results of the study show that bureaucracy in Indonesia is still far from the principles of good governance because it is still patrimonialistic which is characterized as inefficient, ineffective and not objective. Overcoming this bureaucratic pathology can be carried out including global administrative reform, establishing clear legal and regulatory forces and creating a system of accountability and transparency. For the Cianjur Regency Population and Civil Registry Service in reducing bureaucratic pathology by eliminating service discrimination, providing good responses and simplifying services.